2011
DOI: 10.1097/brs.0b013e3181dbfe40
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of the Ball-Tipped Probe for Detecting Pedicle Screw Tract Violations Prior to Instrumenting the Thoracic and Lumbar Spine

Abstract: The standard ball-tipped probe was much less reliable than expected. This technique can be used to confirm an intact pedicle but has an unacceptably high false-positive rate and should be used with caution. Our study suggests that overconfidence in pedicle probing might be dangerous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…An almost universally practised method of probing the pedicle tract with a ball-tipped probe has been shown to have a relatively poor accuracy, with medial breaches as high as upto 32% being missed out on the same [13]. Hence a combination of methods would yield a cumulative outcome of reasonably high accuracy and hence, safety.…”
Section: Discussionmentioning
confidence: 99%
“…An almost universally practised method of probing the pedicle tract with a ball-tipped probe has been shown to have a relatively poor accuracy, with medial breaches as high as upto 32% being missed out on the same [13]. Hence a combination of methods would yield a cumulative outcome of reasonably high accuracy and hence, safety.…”
Section: Discussionmentioning
confidence: 99%
“…Manual pedicle palpation with a ball-tip probe has low accuracy 25,26 and the potential for inadvertent neurological injury with the probe. 27 Even stereotactic image guidance cannot entirely prevent pedicle perforations. 28 Electrical neuromonitoring adds cost and time to surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if the surgeon detects a breach during manual palpation, he or she may opt to 1) place a screw with a diameter smaller than originally planned, 2) revise the track by using the gearshift to create a secondary track along an alternate trajectory within the pedicle, or 3) abandon placing a screw in that particular pedicle altogether. 7,10,12,13,17 Despite widespread use of this method, few studies have focused on the accuracy of manual palpation of thoracic pedicle screw tracks to detect any violation in the cortical margins of the pedicle. 11,17 Of the two studies we are aware of, one concluded that the "standard ball-tipped probe was much less reliable than expected."…”
mentioning
confidence: 99%
“…7,10,12,13,17 Despite widespread use of this method, few studies have focused on the accuracy of manual palpation of thoracic pedicle screw tracks to detect any violation in the cortical margins of the pedicle. 11,17 Of the two studies we are aware of, one concluded that the "standard ball-tipped probe was much less reliable than expected." 17 Besides this conclusion, there was considerable variability between their surgeons with respect to correctly identifying pedicle track placements.…”
mentioning
confidence: 99%
See 1 more Smart Citation